2016
DOI: 10.1111/1759-7714.12345
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of RelB overexpression in non‐small cell lung cancer patients

Abstract: BackgroundLung cancer is a major public health issue in most countries, including China. The expression of RelB is associated with poor prognosis in diverse cancers. However, whether RelB expression could be an indicator of poor prognosis in non‐small cell lung cancer (NSCLC) is still unclear.MethodsThe expression of RelB in NSCLC tumor tissue and adjacent non‐neoplastic tissues were examined by immunohistochemistry. Chi‐square or two‐tailed Fisher's exact tests were used to analyze possible associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
2
20
1
Order By: Relevance
“…Also, patients with higher expression of RELB had decreased RFS and OS in ER-positive breast carcinoma [67]. Moreover, in other tumors such as lung cancer, the expression of NIK and RELB was associated with metastasis and shorter OS [68,69]. These studies are contrary to what we have observed regarding NIK and RELB mRNA expression.…”
Section: Discussioncontrasting
confidence: 58%
“…Also, patients with higher expression of RELB had decreased RFS and OS in ER-positive breast carcinoma [67]. Moreover, in other tumors such as lung cancer, the expression of NIK and RELB was associated with metastasis and shorter OS [68,69]. These studies are contrary to what we have observed regarding NIK and RELB mRNA expression.…”
Section: Discussioncontrasting
confidence: 58%
“…We noticed that some clinical studies reporting NF-jB expression detected by IHC that they correlated with clinicopathological characteristics and/or survival in lung cancers had conflicting results; summarized in Table 3 [7][8][9][10][11][12][13][14][15]. The Rel protein family members can form up to 15 different dimers through combinatorial associations, and various antibodies for different key NF-jB pathway components, such as p65, p105, IjBa and IKKa/b, were used for the evaluation of NF-jB expression in the different studies [6].…”
Section: Discussionmentioning
confidence: 99%
“…The same series of studies have correlated NF-jB expression with clinicopathological characteristics and survival, but the results have been inconsistent. In addition, in most studies, pathologic studies of NF-jB expression were detected by assaying for single components of the NF-jB pathway, and using different anti-NF-jB subunit antibody clones, judgement criteria and cut-off values for assessing NF-jB expression were used in the various studies [6][7][8][9][10][11][12][13][14][15]. Actually, different NF-jB dimers may have different functions, especially the p50-p50 homodimer, which lacks a transactivation domain in the C-termini and has no intrinsic ability to activate transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Cells on the upper surface of the inserts were completely wiped off with a cotton swab, while cells that migrated to the underside of the inserts were fixed with 4% paraformaldehyde for 15 minutes at room temperature. Cells were then stained with 0.5% crystal violet in 20% methanol for 30 minutes, washed three times with distilled water, and visualized with a Leica stereomicroscope (Leica Microsystems, Wetzlar, Germany) . For wound healing assay, cells were grown to 90% confluence in a 12‐well plate, and a scratch wound was created in the monolayer using a pipette tip.…”
Section: Methodsmentioning
confidence: 99%